Dampak Penerapan Etika Bisnis Islam Terhadap Penjualan: (Studi Kasus Pelaku Muslim Di Pasar Sukowono) - Yassir Arafat (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2021)
Buying and selling must not be done based on one's own wishes and methods which can cause harm to other people. Islam is always based on values ​​and ethics in all aspects of human life as a whole, including discourse on buying and selling, however buying and selling has regulations in Islamic law which are sourced from the Qur'an and Sunnah. Based on the background above, the author is interested in studying further by conducting a scientific research entitled: "The Impact of Implementing Islamic Business Ethics on Sales (Case Study of Muslim Actors in Sukowono Market)". The problem formulation in this research is: 1. How is business ethics applied in buying and selling transactions at the Sukowono market? 2. How is Islamic business ethics applied in buying and selling transactions at Sukowono Market? The method used in this research is a qualitative descriptive method using an Islamic economic approach which includes a discussion of buying and selling in Islam and a psychological approach, namely an approach to the problem to be studied. The data collection techniques used were observation, interviews and documentation. Based on the results of the research and discussions that have been carried out, several conclusions can be drawn from the research on the application of Islamic business ethics in buying and selling transactions at Sukowono Market, Sukowono District, Jember Regency. Based on the results of observations obtained from traders and buyers at Sukowono Market when viewed from the four indicators General business ethics is used as a benchmark. The application of business ethics in general has not been implemented well by traders at Sukowono Market because only legal indicators and indicators of religious teachings have been implemented well. Meanwhile, the economic indicators and ethical indicators of each business actor have not been implemented properly by traders at Sukowono Market.